ANALISIS PENGUASAAN KETERAMPILAN PROSES SAINS PADA SISWA KELAS XI SMA NEGERI 9 PEKANBARU - Fitriauspita, Winda; Ma’ruf, Zuhdi; Islami, Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was aimed to describe the level of sains process skill at the second year students of IPA program of SMA 9 Pekanbaru. This research was a survey research. The result of the data analysis used descriptive analysis which described the level of student’s sains process skill. The subject of this research was 109 students of IPA program at the second year. The data gotten from this research was in average percentages of the mastering of science process skills with indikator observing, classifying, interpreting, predicting, asking question, hypotheses, planning the experiment, apply the concept, and communicate. The data analysis result show that the average percentages of each indikators as follows: 83,49% for observing skills, 80,73% for classification skills, 63.00% for interpreting skills, 88,99% for prediction skills, 54,13% for skills of asking questions, 13,76% for hypothetical skills, 65,14% for skill of planning the experiment, 62,39% for skills applying concepts, and 74,01% for communication skills. The overall percentages of the students’ process science skill is 65,07% categorized good. It prove that the mostering of the science process skill of students is be usually higher.Key words: Science Process Skills